2021
DOI: 10.2138/am-2021-7507
|View full text |Cite
|
Sign up to set email alerts
|

Thermal metamorphic history of Antarctic CV3 and CO3 chondrites inferred from the first- and second-order Raman peaks of polyaromatic organic carbon

Abstract: compared to CO3.4-CO3.6 (20 C), which may indicate that the graphitization and structural ordering of carbon reach a critical temperature regime around petrologic type CO3.3.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 9 publications
(21 citation statements)
references
References 54 publications
2
19
0
Order By: Relevance
“…Characterization of such lithologies and their content requires novel analytical techniques. High spatial resolution spectroscopic techniques such as Raman microspectroscopy (micro-Raman; Wang et al 1999;Busemann et al 2007;Fries and Steele 2008;Yesiltas et al 2018Yesiltas et al , 2019Yesiltas et al , 2020 and Fourier transform infrared nanospectroscopy (nano-FTIR; Dominguez et al 2014;Kebukawa et al 2019) have the potential to reveal meteoritic organic and inorganic components in great detail via their active vibrational modes. Confocal Raman spectroscopy provides chemical mapping in two dimensions as well as three-dimensional tomographic imaging capability with micrometer resolution, while the nano-FTIR spectroscopy allows collection of infrared spectra from spots with~20 nm spatial resolution.…”
Section: Introductionmentioning
confidence: 99%
“…Characterization of such lithologies and their content requires novel analytical techniques. High spatial resolution spectroscopic techniques such as Raman microspectroscopy (micro-Raman; Wang et al 1999;Busemann et al 2007;Fries and Steele 2008;Yesiltas et al 2018Yesiltas et al , 2019Yesiltas et al , 2020 and Fourier transform infrared nanospectroscopy (nano-FTIR; Dominguez et al 2014;Kebukawa et al 2019) have the potential to reveal meteoritic organic and inorganic components in great detail via their active vibrational modes. Confocal Raman spectroscopy provides chemical mapping in two dimensions as well as three-dimensional tomographic imaging capability with micrometer resolution, while the nano-FTIR spectroscopy allows collection of infrared spectra from spots with~20 nm spatial resolution.…”
Section: Introductionmentioning
confidence: 99%
“…This is consistent with low petrologic type chondrites (such as types 1 and 2, which experienced thermal metamorphic temperatures of ≤ 150 °C 61 ), evident from the fact that the majority of previous studies showed the presence of carbonyls in those types of chondrites. However, we have shown the presence of abundant carbonyls in DOM 08006, a slightly more heated petrologic type 3.0 CO chondrite whose Raman carbon geothermometry calculation points to peak metamorphic temperatures of ~ 220–230 °C 44 . This suggests a pathway through which aldehyde and carboxylic acids can form and remain intact under such elevated temperatures.…”
Section: Discussionmentioning
confidence: 72%
“…Post-accretionary processes may also be responsible for the absence of carbonyls in QUE 93744. For instance, the peak metamorphic temperature of QUE 93744 was reported to be ~ 430–490 °C, twice as high as that for DOM 08006 44 . Such elevated temperatures might alternatively be responsible for the absence of carbonyls in QUE 93744.…”
Section: Resultsmentioning
confidence: 99%
“…Estimated peak metamorphic temperatures are shown on top of (b). CV3 and CO3 data are from Yesiltas et al CM2 and CR2 data are from Busemann et al…”
Section: Resultsmentioning
confidence: 99%
“…We first removed artificial fluorescence background from the spectra by subtracting a polynomial with a shape size of 200 and a noise factor of 2. To derive Raman spectral parameters of the first order carbon bands, we fitted the background-removed spectra with a pair of Lorentzian functions (e.g., refs , , , and ).…”
Section: Methodsmentioning
confidence: 99%